Simulasi Saham Berbasis Web dengan Teknologi Virtual Private Network di Portal Www.Kontan.Co.Id - Albert Verasius Dian Sano (ComTech: Computer, Mathematics and Engineering Applications, 2011)
The objective of this research is to develop a web-based-online-stock-simulation application applying Virtual Private Network (VPN) technology. The web-based application is prefered for user’s convenience and comfort since it does not require any software to be installed on the client side and is also accessable anywhere and anytime with internet connection availability. The application is developed by means of analysis and design towards the technology needed to establish the connectivity between servers through internet as well as database analysis and design. The data are real time derived from the Indonesia Stock Exchange (IDX) and forwarded through an official data vendor PT XYZ. Data from the IDX will be captured by a middleware application at PT XYZ and forwarded to www.kontan.co.id. This application has been tested and succesfully run by around 700 users. This tool is expected to provide a kind of education and motivation to beginner-level investors who want to be engaged with the stock-trading activities.